SEAFLOOR SLOPES AT MID-OCEAN RIDGES FROM SUBMERSIBLE OBSERVATIONS AND IMPLICATIONS FOR INTERPRETING GEOLOGY FROM SEAFLOOR TOPOGRAPHY - Mitchell N.C.; Tivey M.A.; Gente P. (My University, 2000)
Observations from 145 submersible dives are used to create a database of mid-ocean ridge scarp topography and lithology. Seafloor lithologies are classified into extrusives, basaltic talus, dykes, gabbros and serpentinites, and the dive locations are broadly classified according to whether they are close to transform valleys and as a function of ridge spreading rate. The database is used to determine whether there is any difference in the maximum slope for each rock type, which might relate to differences in rock jointing, cohesion or friction properties. There is a common perception that lower crustal rocks form steeper slopes than shallower crustal rocks but until now there has been little evidence to support or refute this idea. From our analysis we find a tendency for gabbro and dykes to form steeper slopes than serpentinite. The 90th percentile of each lithology slope distribution, used as a measure of limiting slope, is 43°, 39° and 32° for gabbro, dykes and serpentinite, respectively. Lithologic control on slope is weak, however, compared to overall slope variability in these mid-ocean ridge settings so seafloor relief is likely to be a poor guide to underlying geology. We speculate on the structure of eroding fault scarps, outline the implications for attempts to infer active faults from talus ramp activity and discuss more generally factors affecting the geomorphology of mid-ocean ridge slopes.
Keywords: MID-OCEAN RIDGES; OCEAN FLOORS; SCARPS; MARINE GEOLOGY